In vivo Antiphytoviral Activity of Essential Oils and Hydrosols From Origanum vulgare, Thymus vulgaris, and Rosmarinus officinalis to Control Zucchini Yellow Mosaic Virus and Tomato Leaf Curl New Delhi Virus in Cucurbita pepo L. - Taglienti, Anna; Donati, Livia; Ferretti, Luca; Tomassoli, Laura; Sapienza, Filippo; Sabatino, Manuela; Di Massimo, Gaia; Fiorentino, Simona; Vecchiarelli, Valerio; Nota, Paolo; Ragno, Rino (Frontiers in Microbiology, 2022)
In the last decades, the interest in biological activity of natural compounds has been growing. In plant protection, essential oils have been reported to exhibit antiviral, antimycotic and antiparasitic activities, and are regarded as promising for the formulation of safe antimicrobial agents. Attention has also been focused on hydrosols, the essential oils hydro-distillation by-products. Their production is easy, fast and cheap, and they seem to arise less concern for human health than essential oils. Plant viruses represent a major concern for agricultural crops, since no treatment compound is available for virus control. This work was aimed at evaluating the antiphytoviral effectiveness of treatments with three essential oils and corresponding hydrosols extracted from Origanum vulgare, Thymus vulgaris and Rosmarinus officinalis on Cucurbita pepo plants infected by zucchini yellow mosaic virus or tomato leaf curl New Delhi virus. Treatments were applied either concurrently or after virus inoculation, to ascertain an inhibition or curative activity, respectively. Symptoms were observed and samplings were performed weekly; virus titer and expression levels of phenylalanine ammonia lyase gene (PAL) were measured on treated and untreated infected plants by real-time PCR. PAL gene plays an important role in plant defense response, being involved in tolerance/resistance to phytopathogens. Results indicated that treatments were effective against tomato leaf curl New Delhi virus whether applied simultaneously with the inoculation or after. A major inhibition was observed with O. vulgare essential oil and hydrosol, resulting in 10-4-fold decrease of virus titer three weeks after treatment; curative activity gave maximum results with all three essential oils and T. vulgaris and R. officinalis hydrosols, recording from 10-2-fold decrease to virus not detected four weeks after treatment. An induction of PAL gene expression was recorded at 12 d.p.i., then it was restored to the levels of untreated control; this allows to hypothesize an early plant defense response to virus infection, possibly boosted by treatments. Plant extracts’ composition was characterized by gas chromatography-mass spectrometry. Phenols were largely main components of O. vulgare and T. vulgaris extracts (carvacrol and thymol, respectively), while extracts from R. officinalis were based on monoterpene hydrocarbons (essential oil) and oxygenated monoterpenes (hydrosol).